Identifikasi Risiko Penerapan E-Ticketing (pada perum damri cabang Lampung) - Widya, Astriza (Jurnal Kompetitif Bisnis, 2021)
Identifying an e-ticketing application in the application requires risk management, where the variables involved in the calculation are technology risk, financial risk and operational risk. The purpose of this study is to identify the risks associated with the implementation of e-ticketing. This type of research is mixed methods. Research starts from identification, analysis and risk response. Data collection started from interviews, questionnaires and observations. The assessment stage uses the severity index method where the probability indicator is multiplied by the impact where there are 13 indicators from the three variables. Interview with Damri staff and consumers to get more in-depth answers regarding the risks at hand so far. The results of the analysis have found that there are 7 dominant risks including server failure, the community is not familiar with technology, the community does not have the Damriapps and Traveloka applications, data storage errors at Damri Pusat, incorrect seat numbers from applications with agents, payments in the village are not adequate, errors technical. and if left alone will have an impact on the application of e-ticketing. After the risk is known, a risk response is carried out to minimize or negate the impact of these risks. Key Word : Risk Identification, Severity Indexs